Calcined Aceh Bovine Bone (Bos indicus) Intercalated Lithium as An Inorganic Base Catalyst for Transesterification of Castor Oil - Muliadi Ramli; Saiful Saiful; Febriani Febriani; Amraini Amraini; Fathurrahmi Fathurrahmi; Shellatina Shellatina; Cut Fatimah Zuhra (Graduate Program of Syiah Kuala University, 2020)
Realizing abundant availability of local bovine bone wastes in Aceh Province, Indonesia, this study is subjected to take competitive advantages from the local bovine bone waste for preparing an inorganic catalyst preparation. In detail, calcined Aceh bovine bones were successfully intercalated lithium through an impregnation method resulting in the inorganic base catalyst, which showed promising activity in the transesterification of castor oil. Prior to the experiment, the Aceh bovine bone waste was calcined at 900 oC in the air atmosphere for 4 hours, led to forming crystalline phases of hydroxyapatite [Ca5(PO4)3(OH)] and calcium oxide [CaO]. Also, the chemical modification of calcined bovine bone with lithium precursor has enhanced the physicochemical properties of the inorganic base catalyst. Finally, the intercalated Aceh bovine bone has shown a feasible activity in transesterification of castor oil into biodiesel, which yielding methyl ricinoleate as the main product.